Integrative Analysis of the Methylome, Transcriptome, and Proteome Reveals a New Mechanism of Rapeseed Under Freezing Stress - Guoqiang Zheng; Zigang Liu; Jinxiong Wang; Jiaping Wei; Xiaoyun Dong; Hui Li; Ying Wang; Haiyang Tian; Zefeng Wu; Junmei Cui (Agronomy)
Winter rapeseed is susceptible to freezing stress during winter, making it difficult to overwinter safely and resulting in a reduction of yield and quality. DNA methylation, the main epigenetic modification, can regulate plant responses to various stresses. However, the regulatory mechanism of DNA methylation in response to freezing stress in winter rapeseed remains unclear. This study investigates how DNA methylation regulates gene expression and protein abundance in response to freezing stress, revealing key regulatory pathways involved in rapeseed cold tolerance. A total of 6776 unique differentially methylated genes (DMGs), 4285 unique differentially expressed genes (DEGs), and 269 unique differentially abundant proteins (DAPs) were identified between the two cultivars under T1 and T2 freezing stress. Function enrichment analysis revealed that these genes were involved in signal transduction, biosynthesis of unsaturated fatty acids, sugar metabolism, peroxidase, peroxisome, photosynthesis, and additional pathways. An integrative analysis of methylome, transcriptome, and proteome showed that only nine genes were shared among all three datasets, and they were closely related to cold tolerance metabolism in rapeseed. The findings provide molecular insights into rapeseed freezing tolerance, which can be applied in breeding programs to enhance cold resistance in oilseed crops.